Efektivitas Integrasi Nilai-nilai Islam dalam Pendidikan Karakter untuk Pembentukan Generasi Emas: Effectiveness of the Integration of Islamic Values in Character Education for the Formation of the Golden Generation - Budi Johan; Nurul Aliyah; Naila Adystia Paramita; Annisa Salsabila; Eka Fitriyani; Jamaluddin Ramadhan (Litera Academica Publishing, 2025)
Character education based on Islamic values is an effective approach in forming a golden generation that is academically intelligent, has strong moral and spiritual character, and is able to face the challenges of the times with a religious attitude and character. The integrity of Islamic values in character education can strengthen students' moral, ethical and noble values. This research uses qualitative methods and literature study to understand the role of Islamic religious education in shaping the character of the younger generation. The research results show that education based on Islamic values can be a strategic foundation in creating a golden generation with noble character, toughness, and ready to face the dynamics of life in the future. Synergy between schools, families and communities is very important in supporting this effort. Thus, character education based on Islamic values can be a solution to forming a superior Islamic generation with noble morals.